Impact of interfractional motion on hypofractionated pencil beam scanning proton therapy and VMAT delivery for prostate cancer. Issue 9 (6th August 2018) - Moteabbed, Maryam; Trofimov, Alexei; Khan, Fazal H.; Wang, Yi; Sharp, Gregory C.; Zietman, Anthony L.; Efstathiou, Jason A.; Lu, Hsiao‐Ming
Abstract : Purpose: Hypofractionated radiotherapy of prostate cancer is gaining clinical acceptance given its potential increase in therapeutic ratio and evidence for noninferiority and lack of added late toxicities compared to conventional fractionation. However, concerns have been raised that smaller number of fractions might lead to larger dosimetric influence by interfractional motion. We aim to compare the effect of these variations on hypofractionated pencil beam scanning (PBS) proton therapy and volumetric modulated arc therapy (VMAT) for localized prostate cancer. Methods: Weekly CT images were acquired for 6 patients participating in a randomized clinical trial. PBS plans featuring bilateral (BL) and a combination of lateral and anterior‐oblique beams (AOL), and VMAT plans were created. All patients were treated to a conventional 79.2 Gy total dose in 44 fractions. For this study, hypofractionated dose to the prostate gland was 51.6 Gy in 12 fractions or 36.25 Gy in 5 fractions, and 32.8, and 23.1 Gy to proximal seminal vesicles, respectively. Patients were simulated with endorectal balloons to aid gland immobilization. Three fiducial markers were implanted for setup guidance. All plans were recomputed on the weekly CT images after aligning with the simulation CT. The entire set of 9 CT images was used for dose recalculation for 12‐fraction and only 5 used for the 5‐fraction case. Adaptive range adjustments were applied to anterior‐oblique beams assuming clinical availability of in vivo range verification. Fractional doses were summed using deformable dose accumulation to approximate the delivered dose. Biologically equivalent dose to 2 Gy(EQD2) was calculated assuming α / β of 1.5 Gy for prostate and 3 Gy for bladder and rectum. Results: The median delivered prostate D98 was 0.13/0.14/0.13 Gy(EQD2) smaller than planned for PBS‐BL, 0.13/0.27/0.17 Gy(EQD2) for PBS‐AOL and 0.59/0.66/0.59 Gy(EQD2) for VMAT, for 44/12/5 fractions, respectively. The largest D98 reduction was 1.5 and 3.5 Gy(EQD2) for CTV1 and CTV2, respectively. Target dose degradation was comparable for all fractionation schemes within each modality. The maximum increase in rectum D2 was 0.98 Gy(EQD2) for a 5‐fraction PBS case. Conclusions: The robustness of PBS and VMAT were comparable for all patients for the studied fractionations. The delivered target dose generally remained within clinical tolerance and the deviations were relatively minor for both fractionation schemes. The delivered OAR dose stayed in compliance with the RTOG hypofractionation constraints for all cases.